2018
DOI: 10.1536/ihj.17-234
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Presence or Severity of Coronary Artery Disease and Pericardial Fat, Paracardial Fat, Epicardial Fat, Visceral Fat, and Subcutaneous Fat as Assessed by Multi-Detector Row Computed Tomography

Abstract: The associations between the presence or severity of coronary artery disease (CAD) and measurements of various kinds of fat as assessed by multidetector row computed tomography (MDCT) are unclear. We enrolled 300 patients who were clinically suspected to have CAD or who had at least one cardiac risk factor and had undergone MDCT. The number of significantly stenosed coronary vessels (VD), and measurements of pericardial fat index, paracardial fat index, epicardial fat index, visceral fat index, and subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
0
22
0
5
Order By: Relevance
“…In addition to its significant negative correlation with Rentrop scores, VFI (cut off value > 9) was also shown to predict the likelihood of poor CCC with a sensitivity of 95.38% and a specificity of 85.71%. Likewise, in a past study comparing the levels of pericardial fat index, paracardial fat index, and visceral fat index in patients with vs. without CAD, the levels of these fat indices were shown to be significantly higher in the CAD group and positively correlated with the number of significantly stenosed coronary vessels and the Gensini score in CAD patients (51).…”
Section: Discussionmentioning
confidence: 82%
“…In addition to its significant negative correlation with Rentrop scores, VFI (cut off value > 9) was also shown to predict the likelihood of poor CCC with a sensitivity of 95.38% and a specificity of 85.71%. Likewise, in a past study comparing the levels of pericardial fat index, paracardial fat index, and visceral fat index in patients with vs. without CAD, the levels of these fat indices were shown to be significantly higher in the CAD group and positively correlated with the number of significantly stenosed coronary vessels and the Gensini score in CAD patients (51).…”
Section: Discussionmentioning
confidence: 82%
“…Our study indicates that DM patients have more EFT than non-DM patients, and this provides new ideas for the diagnosis and treatment of DM in the future and research into DM performed in the future. EFT is closely related to the occurrence of CHD [63,64]. The difference in EFT between DM patients and non-DM patients may have an important relationship with the incidence of cardiovascular diseases, but whether EFT can be used to assess the risk of cardiovascular diseases in DM patients at an early stage needs to be confirmed by further studies.…”
Section: Future Directionsmentioning
confidence: 99%
“…It has been reported that metabolic syndrome is closely associated with incident CVD. [12][13][14][15][16][17] Although both uric acid levels and metabolic syndrome are associated with CVD, only a small number of studies have evaluated the association between uric acid levels and metabolic syndrome. In the present study, the relationship between uric acid levels and incident metabolic syndrome in a Japanese general population was examined using a discrete proportional hazards regression model.…”
mentioning
confidence: 99%